Chinese Consumers’ Perception of Organic Food and the Associated Purchase Behavior - Chen, Hailin; Zhou, Joyce; Yu, Jun (Journal of Marketing Development and Competitiveness, 2022)
Organic food is a relatively new phenomenon in China, one of the largest consumer markets. The purpose of this research is to explore Chinese consumers’ perception of organic food and the associated purchase behavior. To this end, a survey was conducted among Chinese consumers. Findings indicate there is some acceptance of organic food products among Chinese consumers based on their beliefs of the benefits of these products. However, current interest in buying organic food products is not high. The findings have potential to help organic food businesses seek out new market opportunities, improve product positioning, and select the most effective channels of distribution. Implications for both future research and marketing practice are discussed.